The Impact of Palm Plantations on the Economy, Social and Environmental - Elfandra Fan Fadhli Rabbi; Abdul Razak; Nurhasan Syah; Skunda Diliarosta (Postgraduate School, Universitas Negeri Padang, 2023)
This paper aims to describe the forms of impacts caused by oil palm plantation activities from economic, social, and environmental aspects. The method used by the author is a literature review related to the economic, social, and environmental impacts caused by oil palm plantation activities. A library study is a study whose research object is in the form of literature works in the form of scientific journals, books, articles in the mass media, as well as statistical data. After the resulting impacts are known, the author's hope of this paper is that the positive impacts generated by oil palm plantation activities can be maximized and the negative impacts on the environment can be minimized. The negative impact on the environment is not felt directly but in the long term. So that the community will be more prosperous without damaging the environment. In the end, sustainable development can be realized collectively.